Elucidation of the Formation Mechanism of 2-Mercapto-3-Methyl-1-Butanol in Beer. Part I: Identification of the Key Factors during Fermentation. (16th September 2020) - Noba, Shigekuni; Kikuchi, Kaori; Yako, Nana; Irie, Taku; Kobayashi, Minoru; Uemura, Kazuhiko
Abstract: 2-Mercapto-3-methyl-1-butanol (2M3MB) imparts an onion-like off-flavor to beer and is believed to result from the hot aeration of brewer's wort. However, little has been reported regarding the mechanism of formation of 2M3MB. In this study, the origin of a 2M3MB precursor (2, 3-epoxy-3-methylbutanal, EMB) and the mechanism of formation of 2M3MB from EMB were investigated. EMB was generated by oxidation of the side chain of iso-alpha acids from the hops. It was revealed that EMB reacts with hydrogen sulfide to give 2-mercapto-3-hydroxy-3-methylbutanal, which is then converted into 2M3MB by yeast. When the concentrations of these compounds were measured during beer fermentation using gas chromatography/mass spectrometry, it became clear that only a portion of EMB was converted into 2M3MB, since the majority of EMB was reduced to 2, 3-epoxy-3-methylbutanol without conversion to 2M3MB.